A case study of para table tennis athlete's functional ability - Lim, D.; Bin, Y.; Tan, Z.; Li, H.; Teng, P. (Proceedings of the 3rd International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2015)
Reach is an important performance aspect for para table tennis athletes under the seated classifications of 1 and 2. The aim of this pilot study was to define the effective reach of Class 1 and 2 para table tennis athletes. Three players, 3 from Class 1 and 2 took part in this investigation. During the static assessment, players were asked to perform full reach from a seated position across the table tennis table, with the area outlined as Sweep Area (SA). In the dynamic assessment, players hit a series of balls propped up along the perimeter of the SA. The average SA for Class 1 and 2 were 0.560±0.08m2 and 0.640±0.04m2 respectively. The average Right and Left Tipping Angle (RTA, LTA) on the frontal plane were ±20.7° and ±22.0° for Class 1, and 49.3° and 36.0° for Class 2. Class 1`s average Sweep Time (ST) was 4.92±0.98s, whereas Class 2`s average ST was 3.69±0.58s. There is a difference in RTA between Class 1 and 2 players. For future work more samples are needed to understand the a thletes` Range of Motion (ROM). Findings will serve as important considerations for training design, game strategy and equipment usage.